Perceptions of HIV patients on the use of cell phones as a tool to improve their antiretroviral adherence in Northwest, Ethiopia: a cross-sectional study - Sefefe Birhanu Tizie; Atsede Mazengia Shiferaw; Miftah Abdella Beshir; Muluken Belachew Mengistie; Sayih Mehari Degualem; Bayou Tilahun Assaye (BMC, 2023)
Abstract Background Human immuno deficiency virus (HIV) is one of the most infectious diseases that cause death. A Medication non-adherence in HIV patient has been caused by factors such as not taking medications as prescribed by a physician, withdrawing from medication, missing appointments, and forgetfulness. To improve patients' antiretroviral adherence, supporting them with mobile phone applications is advisable. This study aimed to assess HIV patients' perceptions towards the use of cell phones to improve antiretroviral adherence. Methods and materials An institutional-based cross-sectional study was conducted among 423 HIV patients at a comprehensive specialized hospital in northwest Ethiopia from June to July 2022. Study participants were selected using systematic random sampling techniques and the data collection tool was adopted and modified for different literatures. Data were collected through an online data collection tool, and STATA-14 software was used for analysis. Descriptive statistics and binary logistic regression were used. The variables with a P-value equal to or less than 0.2 in bivariable logistic regression were entered into a multivariable logistic regression, and model fitness was assessed. Results A total of 410 study subjects have participated, making a response rate of 97%. In this study, 62% (95% CI: 57-67%) of HIV patients had a positive perception regarding the use of mobile phones to improve antiretroviral adherence. Perceived usefulness of mobile phones [AOR = 4.5, (95% CI: 2.2-9.1)], perceived ease of mobile phone use [AOR = 3.9, (95% CI: 2.0-7.5), age [AOR = 3.0, (95% CI: 1.5-6.2)], and educational status [AOR = 5.0, (95% CI: 2.3-10.0)] were significantly associated with HIV patients' perception of mobile phones' use to improve antiretroviral adherence. Conclusions More than half of the respondents had positive perception regarding the use of mobile phones to enhance their adherence to treatment. Perceived usefulness, perceived ease of use, age, and educational status was significantly associated with perception of mobile phone use to enhance antiretroviral therapy adherence. Therefore, the government have to encourage and support patients in incorporating mobile phones into their antiretroviral therapy (ART) follow-up through training.